Bioactivities and phytochemical profile of Cyclosorus parasiticus from East Java, Indonesia via GC-MS and LC-MS - FUAD BAHRUL ULUM; DWI SETYATI; IKA OKTAVIANAWATI; MOH. IKMAL ALFI RIZQONI; ERLIN NOVITA SARI; KAHAR MUZAKHAR; MUKHAMAD SU’UDI (Biodiversitas Journal of Biological Diversity, 2026)
Abstract. Ulum FB, Setyati D, Oktavianawati I, Rizqoni MIA, Sari EN, Muzakhar K, Su’udi M. 2026. Bioactivities and phytochemical profile of Cyclosorus parasiticus from East Java, Indonesia via GC-MS and LC-MS. Biodiversitas 27 (2): d270234. https://doi.org/10.13057/biodiv/d270234. Cyclosorus parasiticus is a terrestrial fern abundantly distributed in the area of Gumitir Mountain, East Java, Indonesia. Despite its ecological abundance, its pharmacological potential remains undercharacterised, although leaf tissues from Gumitir populations accumulate relatively high levels of flavonoids and alkaloids. Through an integrative bioassay–metabolomics approach, this study presents the first systematic evaluation of the antibacterial and antioxidant activities, together with comprehensive chemical profiling, of C. parasiticus from the Gumitir region. Metabolite annotation revealed pronounced chemical diversity, with 39 compounds identified by GC-MS and six dominant LC-MS features. Importantly, the diterpene euphornin and the alkaloids canthiumine and haplophytine were detected and are reported here for the first time in a fern, substantially expanding current knowledge of pteridophyte secondary metabolism and highlighting previously overlooked alkaloid diversity in fern taxa. The methanolic extract exhibited concentration-dependent antibacterial inhibition against Staphylococcus aureus, Kocuria rosea, Pseudomonas aeruginosa, and Escherichia coli, with greater susceptibility observed in Gram-positive bacteria. Antioxidant activity measured by the DPPH radical-scavenging assay yielded an IC50 value of 176.66±14.64 ppm, indicating moderate radical-scavenging capacity. Collectively, these findings establish C. parasiticus (Gumitir population) as a chemically rich fern with measurable antibacterial and antioxidant potential, supporting its promise as a natural source of pharmacologically relevant metabolites.